Mengetahui gaya pembelajaran anda untuk pembelajaran berkesan / Prof. Madya Hajah Fuziah Haji Mohd Nadzar - Haji Mohd Nadzar, Fuziah (Faculty of Information Management, 2009)
The concept of learning styles was briefly described. The significance of recognizing one's learning style was outlined. Various learning style models were mentioned. Strategies that students can put into practice to improve their learning were provided.